Navigating social reintegration of children in conflict with law: Postmodern family communication perspective - Aiyub, Aiyub; Yusmanizar, Yusmanizar; Sukmarini, Andi Vita (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
Children in conflict with the law face significant challenges in reintegrating into society, often struggling with stigmatization and a lack of supportive environments. From a postmodern family communication perspective, understanding the dynamics of family relationships and their role in fostering acceptance and growth is crucial for successful social reintegration. This study employed a qualitative approach to understand family communication strategies in supporting the social reintegration of children facing legal issues in Nunukan Regency. The research was conducted in February 2024 at the Department of Social Empowerment for Women and Child Protection. Data were collected through in-depth interviews with parents and Social Department staff, complemented by observation and documentation. The data analysis process involved data reduction, presentation, and conclusion drawing, with validity testing through triangulation. The findings revealed that family communication strategies are crucial in the social reintegration process of children. Open, supportive, and responsive communication from the family helps create a supportive environment during legal proceedings. Key elements in these strategies include awareness of the child's emotional needs, active participation of all family members, clear role and responsibility assignments, and consistent moral and practical support. The synergy between family communication and relevant stakeholders plays a vital role in shaping a better future for these children. Despite challenges, supportive factors strengthen the family’s role as the primary agent in the social reintegration of children facing legal issues. Families play a significant role through supportive communication, providing the emotional and practical support needed for successful reintegration.